High Glucose로 유도된 산화 스트레스에 대한 황칠나무 잎 추출물의 뇌신경세포 보호 효과 - 김종민(Jong Min Kim); 박선경(Seon Kyeong Park); 궈텐쟈오(Tian Jiao Guo); 강진용(Jin Yong Kang); 하정수(Jeong Su Ha); 이두상(Du Sang Lee); 권오준(O-Jun Kwon); 이욱(Uk Lee); 허호진(Ho Jin Heo) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2016)
Antioxidant activities and neuroprotective effects of ethyl acetate fraction from Dendropanax morbifera (EFDM) against high glucose-induced oxidative stress and neurotoxicity were investigated to confirm their physiological activities. An 80% ethanolic extract of D. morbifera showed the highest contents of total phenolic compounds as well as 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) and 1,1-diphenyl-2-picrylhydrazyl radical scavenging activities. The extract was fractionated using several solvents, and the ethyl acetate fraction showed the highest activities in ferric reducing/antioxidant power and malondialdehyde inhibitory assays. To evaluate the neuroprotective effect based on antioxidant activities, cell viability was assessed using PC12 and MC-IXC cells in $H_2O_2$- and high glucose-induced cytotoxic assays, respectively. EFDM evidently showed neuroprotective effects in all cells (neuron-like PC12 cells and human brain-originated neuroblastoma MC-IXC cells). Inhibitory effect of the extract on acetylcholinesterase (AChE) as an acetylcholine-hydrolyzing enzyme was performed to examine the effect on cognitive function. EFDM presented an AChE inhibitory effect. Finally, high-performance liquid chromatography analysis showed that the major phenolic compound of EFDM is probably a rutin. 본 연구는 한국 고유 식용 자원인 황칠나무의 잎을 이용한 항산화 효과 및 고혈당으로 인한 신경/뇌신경세포 보호 효과를 알아보고자 실시하였다. 황칠나무 잎 추출물의 총폴리페놀 함량, ABTS와 DPPH 라디칼 소거 활성을 측정하였으며 활성이 가장 높은 80% 에탄올 추출물을 이용하여 극성 정도에 따라 분획을 하였다. 이들 중 ethyl acetate 분획물이 총 항산화력(FRAP assay)과 지질과산화물(MDA) 생성 억제 활성이 다른 분획물에 비하여 유의적으로 높은 값을 나타냈다. 이를 이용하여 신경세포로서의 PC12 세포와 인간 뇌조직 유래 뇌신경세포로서의 MC-IXC 세포에서 $H_2O_2$와 고혈당에 의한 세포생존율을 측정하였고, ethyl acetate 분획물은 산화적 스트레스로부터의 효과적인 세포 보호 효과를 나타냈다. 또한, 뇌신경말단에서 신경전달물질(ACh)의 분해를 유발하는 효소(AChE)의 저해 효과를 측정하였고, ethyl acetate 분획물은 유의적인 AChE 저해 효과를 보였다. 마지막으로 황칠나무 잎 ethyl acetate 분획물의 생리활성 물질을 확인하고자 HPLC 분석을 하였으며, 주요 생리활성 물질은 rutin으로 추정되었다. 이러한 연구 결과를 바탕으로 고려할 때 황칠나무 잎 추출물은 천연 항산화제의 역할을 가지고 있을 뿐만 아니라 이를 통해 산화적 스트레스로부터 뇌신경세포 등을 효과적으로 보호할 수 있으며 더불어 AChE 저해 활성을 통한 인지기능 개선 가능 소재로서 연구될 수 있을 것으로 판단된다.